Japan's deflationary hangover: Wage stagnation and the syndrome of the ever-weaker yen - Ronald I. McKinnon (Asian Development Bank Institute (ADBI), 2007)
Japan still suffers a deflationary hangover from the great episodic yen appreciations of the 1980s into the mid-1990s. Money wages are still declining, and short-term interest rates remain trapped near zero. After Japan's 'lost decade' from 1992 to 2002, however, output has begun to grow modestly-but through export expansion and associated investment rather than domestic consumption. This export-led growth has been helped by a passive real depreciation of the yen: prices and wages in Europe and the United States have grown, and are growing, faster than in Japan. As the yen becomes weaker in real terms, American and European industrialists and politicians are again complaining that the yen is too weak (Japan bashing II?)-although the pressure on Japan to appreciate is not yet as great as it now is on the People's Republic of China (PRC). But Japan is trapped. If it does appreciate the yen, its fragile economy will be driven back into outright deflation. The only solution is to stabilize the nominal dollar value of the yen over the long term, but this step won't necessarily be immediately effective in placating foreign mercantilists. Under foreign pressure to appreciate the renminbi, the PRC, with its booming economy, is now in a similar position to Japan's of more than 20 years ago. Policy makers in the PRC should resist pressure to go down the same deflationary road as Japan.
Keywords: E31; E58; F31; 330; Deflation; Wechselkurs; Geldpolitik; Japan